(untitled) (Research, Society and Development, 2022)
The growing concern about one of the biggest environmental problems today, air pollution and its effects on the population, resulted in several studies and research to minimize the impacts on global health. This crescent happened after industrial and urban expansion in the mid-nineteenth century, where it ran rampant through the industrial revolution. The challenges to finding a sustainable balance between the diversity of fuels and sources, the costs, and the environmental impact lead to several research fronts. According to the World Health Organization (WHO), in 2019, more than 4 million people died prematurely from pollution. This study discusses the possibilities of ethanol/gasoline blends, engine performance variations, and impacts on the resulting results and gas emissions. The study used a powertrain with Otto cycle engine model K7M from Renault, manufactured in 2008, with approximately 1600 cc, 4-cylinder in-line configuration with two valves each, generating a power of 95 HP, 14.1 mkgf (alcohol) and fuel system through multipoint electronic injection. The teste applied five fuel mixtures – 0%, 25%, 50%, 75%, and 100% of hydrated ethanol in the blend. Results indicated that at low speeds, the CO2 emissions increased as the blend increased. However, the emissions increased considerably when the speed increased. The Nox emissions were irregular in the proportions of the blends. It could be concluded that NOX does not behave linearly, and the best condition is found with the mixture of 75% ethanol, where we reach the lowest points of NOX and HC.